ACUTE KIDNEY INJURY AFTER HEART TRANSPLANTATION: RISK FACTORS AND RENAL REPLACEMENT THERAPY - Y. V. Kopylova; Y. L. Poz; A. G. Strokov; V. N. Poptsov; O. V. Voronina; S. G. Uhrenkov (Вестник трансплантологии и искусственных органов)
Acute kidney injury (AKI) is a frequent complication after heart transplantation (HT). For the identification of risk factors of AKI and optimal modes of renal replacement therapy (RRT) 86 HT data was analyzed. AKI was observed in 37 cases. The main risk factors were renal failure before HT, heart transplant dysfunction and requirement in mechanical support. Continuous RRT was preferable due to the best control of patient’s volumes. The widening of indications for RRT was associated with better survival. In the cases of AKI occurrence the long-term (>10 years) prognosis was worsening significantly.